PRODUCTION OF FUEL PELLETS FROM COCONUT COIR DUST MIXED WITH BIOMASS WASTES - Wichianphong, Napada; Juepanit , Taweesub; Miangkae, Phantipa (PSRU Journal of Science and Technology, 2020)
The objective of this research was to produce biomass fuel pellets from agricultural wastes in order to explore an alternative energy source and disposal of the agricultural waste in community. In this study, dried biomass was compressed with pelletizer machine into small cylindrical pellets with approximately 6 mm in diameter and 1-2 mm in length. The obtained fuel pellets was made from primary raw material as coconut coir dust, an abundantly available waste material found in Bang Kla district of Chachoengsao province, mixed with different kinds of waste, including animal manure from chicken, duck and cow, rice husk, sawdust and mango leaves, at the weight ratio of 60 : 40. In addition, Agro-industrial wastes, such as low-quality tapioca starch rejected and molasses were used as binders in the preparation of pellets. Parameters of the obtained pellets such as heating value, moisture, ash, volatile matter, fixed carbon content were investigated. It was found that the heating value of the obtained fuel pellets was between 3,583-4,225 kilocalories per kilogram (kcal/kg). The pellets made from coconut coir dust mixed with sawdust (60 : 40) using starch paste as a binder provided the highest heating value as 4,225 kcal/kg. Moreover, the other properties of resulting pellets, including moisture, ash and fixed carbon content, were in the range of standard values of community product chunk-compressed charcoal and common charcoal.